ORGANISATIONAL DEVELOPMENT INTERVENTIONS TO SOLVE PERFORMANCE MANAGEMENT CHALLENGES - Dr. Turki Fahed Al Masaeid (PalArch's Journal of Archaeology of Egypt / Egyptology, 2020)
Organisational development is a crucial part of the sustainability and growth of a business. Organisational development can be implemented in business by adapting efficient leadership approach, managing employee performance and designing a clear work process. This report focuses on the issue related to organisational development challenge of performance management in the firm. For this purpose, the potentiality of applying organisational development interventions has also been considered. It is identified that the company is facing challenge in managing performance due to issue in structure, culture and inability to influence employees innovation. To solve the issue, the company can able to apply the organisational development intervention technique through changes in leadership, work culture as well as adoption of structure like flat organisational structure to maintain smooth flow of communication.